Moral Emotions and Moral Disengagement: Concurrent and Longitudinal Associations With Aggressive Behavior Among Early Adolescents. (June 2019) - Mazzone, Angela; Yanagida, Takuya; C. S. Caravita, Simona; Strohmeier, Dagmar
The complex temporal associations among moral disengagement, moral emotions, and aggressive behavior were investigated within a short-term four-wave longitudinal study in a sample of early adolescents (at T1: N = 245; M age = 12.16 years; SD = 0.85). Moral disengagement and aggressive behavior were investigated by validated self-report scales. Shame and guilt were assessed in response to six-story vignettes. A series of four-wave longitudinal mediation analyses were conducted to test several theoretically meaningful models. Mediation models revealed positive reciprocal longitudinal effects between aggressive behavior and moral disengagement. Aggressive behavior negatively predicted moral emotions, and moral disengagement was negatively associated with moral emotions over time. When testing competing models including all three variables in one model, no theoretical meaningful mediation process emerged: Instead, high moral disengagement predicted lower moral emotions but higher aggressive behavior over time. Results are discussed regarding their practical importance for prevention and intervention programs.